Mild Clinical Presentation of Joubert Syndrome in a Male Adult Carrying Biallelic MKS1 Truncating Variants - Raffaella Brunetti-Pierri; Marianthi Karali; Francesco Testa; Gerarda Cappuccio; Maria Elena Onore; Francesca Romano; Giuseppe De Rosa; Enrico Tedeschi; Nicola Brunetti-Pierri; Sandro Banfi; Francesca Simonelli (Diagnostics, 2021)
Pathogenic variants in the MKS1 gene are responsible for a ciliopathy with a wide spectrum of clinical manifestations ranging from Meckel and Joubert syndrome (JBTS) to Bardet-Biedl syndrome, and involving the central nervous system, liver, kidney, skeleton, and retina. We report a 39-year-old male individual presenting with isolated Retinitis Pigmentosa (RP), as assessed by full ophthalmological evaluation including Best-Corrected Visual Acuity measurements, fundus examination, Goldmann Visual Field test, and full-field Electroretinography. A clinical exome identified biallelic nonsense variants in MKS1 that prompted post-genotyping investigations for systemic abnormalities of ciliopathy. Brain magnetic resonance imaging revealed malformations of the posterior cranial fossa with the ‘molar tooth sign’ and cerebellar folia dysplasia, which are both distinctive features of JBTS. No other organ or skeletal abnormalities were detected. This case illustrates the power of clinical exome for the identification of the mildest forms of a disease spectrum, such as a mild JBTS with RP in the presented case of an individual carrying biallelic truncating variants in MKS1.